KAJIAN PENGUKURAN SKALA PENGALAMAN KERAWANAN PANGAN PADA RUMAH TANGGA PERTANIAN: HASIL UJI COBA SURVEI PERTANIAN TERINTEGRASI - Octavia Rizky Prasetyo; Kadir Kadir (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2021)
Food Insecurity Experience Scale (FIES) measurement focusing on agricultural households has not been reported in Indonesia. This study aims to exercise FIES measurement to estimate the prevalence of food insecurity on agricultural households through the pilot of Integrated Agricultural Survey (SITASI) carried out in three provinces, namely West Java, East Java, and West Nusa Tenggara in 2020. The survey observed 1,300 households samples. FIES measurement applied on the survey to estimate the prevalence of food insecurity. Estimation was conducted by making use of the survey weight obtained from a multi-stage random sampling design. The results show that the FIES measurement can be applied to agricultural households through SITASI. All of assumptions underlying the validity of FIES measurement were met. In total, the prevalence rate of moderate or severe food insecurity in the three provinces is only 1.12 % of total agricultural households. Meanwhile, the prevalence of severe food insecurity is only 0.12 %. These findings confirm that the incidence of food insecurity is quite rare in agricultural households. However, in absolute terms, the numbers are quite significant so it needs interventions, among others assistance to improve productivity, scaling-up agricultural cultivation, and social safety nets focusing on the access to food.